Mishima Yukios „Zur Verteidigung unserer Kultur" (Bunka boeiron): Ein japanischer Identitätsdiskurs im internationalen Kontext - Mak, Rebecca (WeltLiteraturen, 2014)
This volume presents Yukio Mishima’s essay "On the Defense of Culture" (1968) for the first time in German translation. Mishima examines the relationship between culture, tradition, the emperor, and nation, and asserts his opinions about these issues, which also shape his fictional works. This volume engages in a close reading of the text, thus illuminating major currents in post-war Japanese intellectual discourse
Keywords: Hochschulschrift; Mishima, Yukio / Bunka bōeiron